Assessing the sufficiency of corporate funding for undergraduate bursaries and their impacts on student access and success in South Africa perspectives and insights from past bursary recipients and corporate social investment (CSI) professionals in Gauteng Province - Thebe, Vusi (University of Pretoria, 2025)
Thesis (PhD (Development Studies))--University of Pretoria, 2024.